Comparative Evaluation Of Aquaporin 1 Expression In Benign And Malignant Salivary Gland Tumors: An Immunohistochemical Study (Applied Biological Research, 2020)
Aquaporin 1 (AQP1) is a water channel protein located on the cell  membranes of several epithelial and endothelial cells, and also significantly  in tumor endothelia. Though the role of AQP1 in tumor progression has  been substantiated sufficiently in past, very few studies have evaluated its immuno-histochemical expression in salivary gland tumors. The current  study comparatively evaluated the AQP1 expression in both benign and  malignant salivary gland tumors in human. The study included a total of  26 cases, 13 cases each from benign and malignant categories. The benign  tumors included were pleomorphic adenoma (12), myoepithelioma (1)  while malignant tumors included mucoepidermoid carcinoma (11),  adenoid cystic carcinoma (1) and adenocarcinoma (1). The study  demonstrated that AQP1 was immunolocalized to the non-luminal ductal  cells in pleomorphic adenoma and adenoid cystic carcinoma. The  intermediate and epidermoid cells of muco-epidermoid carcinoma showed  a weak expression. Negative expression was noticed in myo-epithelioma  and adenocarcinoma. The results showed no significant difference in the  expression of AQP1 between benign and malignant salivary gland tumors; however, it hypothesized that AQP1 is significantly expressed by either  myoepithelial cells or basal cells considering that the non-luminal region  usually comprises these cells in a normal salivary gland.
Keywords: Aquaporin 1; benign salivary gland tumors; malignant salivary gland tumors; immunohistochemistry